Regulating the Polypyrrole Ion-Selective Membrane and Au Solid Contact Layer to Improve the Performance of Nitrate All-Solid Ion-Selective Electrodes - Weizhuo Gao; Weixuan Jing; Yanrui Du; Zehao Li; Pengcheng Liu; Feng Han; Libo Zhao; Zhaochu Yang; Zhuangde Jiang (Micromachines, 2023)
With polymerization duration and Au3+ concentration of the electrolyte regulated, a desirable nitrate-doped polypyrrole ion-selective membrane (PPy(NO3−)-ISM) and Au solid contact layer of anticipate surface morphology were obtained, and the performance of nitrate all-solid ion-selective electrodes (NS ISEs) was improved. It was found that the roughest PPy(NO3−)-ISM remarkably increases the actual contact surface area of the PPy(NO3−)-ISMs with nitrate solution, which leads to better adsorption of NO3− ions upon the PPy(NO3−)-ISMs, and produces a larger number of electrons. The most hydrophobic Au solid contact layer avoids the formation of the aqueous layer at the interface between the PPy(NO3−)-ISM and Au solid contact layer, and ensures unimpeded transporting of the produced electrons. The PPy-Au-NS ISE for polymerization duration 1800 s and at Au3+ concentration 2.5 mM of the electrolyte displays an optimal nitrate potential response, including a Nernstian slope of 54.0 mV/dec, LOD of 1.1 × 10−4 M, rapid average response time less than 1.9 s, and long-term stability of more than 5 weeks. This indicates that the PPy-Au-NS ISE is an effective working electrode for the electrochemical determination of NO3− concentration.